Mesenchymal chondrosarcoma: An Australian multi‐centre cohort study. (23rd May 2022) - Strach, Madeleine C.; Grimison, Peter S.; Hong, Angela; Boyle, Richard; Stalley, Paul; Karim, Rooshdiya; Connolly, Elizabeth A.; Bae, Susie; Desai, Jayesh; Crowe, Philip; Singhal, Nimit; Bhadri, Vivek A.
Abstract: Background: Mesenchymal chondrosarcoma (MCS) is an ultra‐rare sarcoma that follows a more aggressive course than conventional chondrosarcoma. This study evaluates prognostic factors, treatments (surgery, chemotherapy, and radiation), and outcomes in an Australian setting. Methods: We collected demographics, clinicopathological variables, treatment characteristics, and survival status from patients with MCS registered on the national ACCORD sarcoma database. Outcomes include overall survival (OS) and progression‐free survival (PFS). Results: We identified 22 patients with MCS between 2001–2022. Median age was 28 (range 10–59) years, 19 (86%) had localised disease at diagnosis of whom 16 had surgery (84%), 11 received radiation (58%), and 10 chemotherapy (53%). Ten (52%) developed recurrence and/or metastases on follow‐up and three patients with initial metastatic disease received surgery, radiation, and chemotherapy. At a median follow‐up of 50.9  (range 0.4–210) months nine patients had died. The median OS was 104.1 months (95% CI 25.8–182.3). There was improved OS for patients with localised disease who had surgical resection of the primary ( p  = 0.003) and those with ECOG 0–1 compared to 2–3 ( p  = 0.023) on univariate analysis. Conclusions: This study demonstrates contemporary Australian treatment patterns of MCS. The role of chemotherapy for localised disease remains uncertain. Understanding treatment patterns and outcomes help support treatment decisions and design of trials for novel therapeutic strategies. Abstract : This study demonstrates current treatment patterns and clinical outcomes for mesenchymal chondrosarcoma, an ultra‐rare tumour. This helps support treatment decisions and design of trials for novel therapeutic strategies.